Shreds of matter : Cormac McCarthy and the concept of nature - Greve, Julius (Hanover, New Hampshire : Dartmouth College Press, 2018)
"Julius Greve offers a nuanced and innovative take on the writer's ostensible localism and the ecocentric perspective on the world that is assumed by most critics. In opposing both the standard interpretations of McCarthy's novels as either critical of persisting American ideologies--manifest destiny and imperialism--or of the ways in which humanity has wasted Planet Earth, Greve emphasizes the author's interest in the history of science and in the mythographical developments of religious discourse."--
Introduction. Cormac McCarthy's Concept of Nature -- "Trailing the Cord": Literary Descent and the Ethos of Ecology -- "Shreds of Matter": Physiocentrism and Transnational Speculation -- "Cloaca Maxima": Ontological Decay, or the Decomposition of Nature -- "Another Kind of Clay": Physiophilosophy and War -- "Malignant Life": Indifference, Identity, and Narrative Extainment -- "The Ashes of Its Ruin": Writing Nature between Orphism and Prometheanism -- Conclusion. Naturphilosophie and the Literature of Nature.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 10, 2019).
eBooks on EBSCOhost
Keywords: McCarthy, Cormac, -- 1933-2023 -- Criticism and interpretation; McCarthy, Cormac, -- 1933-; Ecology in literature; LITERARY CRITICISM -- American -- General; Ecology in literature; Electronic books; Criticism, interpretation, etc